Emerging Stock Markets after the Crises - John Calverley; Sarah Hewin; Kevin Grice (SUERF - The European Money and Finance Forum, 2000)
The paper analyses the performance of emerging equity markets since 1985 in the light of the Asia crisis. Contrary to the high hopes of many investors, emerging markets have severely under-performed as an asset class over the whole period, (es-pecially since 1994), lagging well behind the US and Europe both in returns and volatility. The paper looks at the factors which have driven emerging markets per-formance and asks why returns have been so poor. It finds that periods of strong gains in particular countries and regions followed major policy transformations, for example with the emergence of the Asian miracle in the 1980's, then Latin America's renaissance in the early 1990's and later, Eastern Europe's emergence. Other major factors that frequently play a role are US interest rates and world growth trends. The emerging market crisis of 1997-8 has damaged the credibility of the Asian miracle and investors now seem to be assigning emerging stocks much higher risk premia than before. One reason for this change is the surprisingly weak relationship between profits growth and GDP growth, which the paper suggests may be due partly to over-invest-ment leading to diminishing profitability and partly deficiencies in corporate governance.
Keywords: 330; Emerging stock markets; Finanzkrise; Schwellenländer; Ostasien; Lateinamerika; Osteuropa